2017
DOI: 10.5114/kitp.2017.72229
|View full text |Cite
|
Sign up to set email alerts
|

The influence of adding tomato extract and acetylsalicylic acid to hypotensive therapy on the daily blood pressure profiles of patients with arterial hypertension and high cardiovascular risk

Abstract: IntroductionArterial hypertension (HT) is one of the most common diseases around the world and constitutes a significant medical, social, and economic problem. Lifestyle changes, including adequate fruit and vegetable consumption, play an important role in controlling blood pressure (BP) and other cardiovascular risk factors.AimTo compare the influence of adding acetylsalicylic acid (ASA) or standardized tomato extract (STE) to standard hypotensive therapy on the values of arterial pressure and the daily blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Some vegetables also showed a protective effect on CVDs. An RCT found that the intake of 213 mg tomato extract for 4 weeks lowered DBP and mean arterial pressure in patients with hypertension and high risk of CVDs [ 105 ]. Moreover, several studies revealed the potent hypotensive efficacy of beetroot which was associated with its high content of nitrate.…”
Section: Clinical Trialsmentioning
confidence: 99%
“…Some vegetables also showed a protective effect on CVDs. An RCT found that the intake of 213 mg tomato extract for 4 weeks lowered DBP and mean arterial pressure in patients with hypertension and high risk of CVDs [ 105 ]. Moreover, several studies revealed the potent hypotensive efficacy of beetroot which was associated with its high content of nitrate.…”
Section: Clinical Trialsmentioning
confidence: 99%
“…Some studies indicated that the bioactive component of tomatoes is lycopene, known to have antioxidant, antihypertensive, and hypolipidemic effects in vitro and in vivo (70,71). In addition, although Thies et al (72) reported that lycopene may also have an effect on blood platelet activation, none of the studies of Fruitflow or ZAAX tomato extract described the concentration of lycopene in the preparations (44,45,47,48,46).…”
Section: Tomato (Solanum Lycopersicum L)mentioning
confidence: 99%
“…Tomato ( Solanum lycopersicum ), a common vegetable, is another example of a natural ACE inhibitor. During the past two years, five clinical trials studying the health impact of tomato extracts on a high cardiovascular risk population pointed to a reduced risk of hypertension or other cardiovascular diseases [127,128,129,130,131]. By exploring the detailed mechanisms, the major bioactive component of tomato, lycopene, was identified as an ACE inhibitor and antioxidant that might be the main substance responsible for its antihypertensive efficacy [132].…”
Section: Physiological Regulation Mechanism In Blood-pressurementioning
confidence: 99%